Influence of Pyrolysis Temperature on the Heavy Metal Sorption Capacity of Biochar from Poultry Manure - Jolanta Sobik-Szołtysek (MDPI AG, 2021)
Sorption properties of various biochars have been extensively investigated by many researchers. One of the parameters that have a significant impact on sorption properties is pyrolysis temperature. This paper presents a study on the effect of pyrolysis temperature (425, 575, 725 °C) on the sorption properties of poultry-manure-derived biochar (BPM). The produced biochars, i.e., BPM425, BPM575 and BPM725, demonstrated specific properties at 425, 525 and 752 °C such as high pH (10.40, 10.65 and 12.45), high ash contents (52.07, 61.74 and 78.38%) and relatively low BET (Brunauer, Emmett and Teller) surface area (11, 17 and 19 m2·g−1). The analysis of the mineral phases of the BPMs confirmed the buffering capacity. The investigated biochars were tested for sorption of Zn, Cd and Pb in mono-, double- and triple-metal batch sorption tests. According to the obtained results, biochar produced at a temperature of 575 °C (BPM575) can function as a sufficient sorbent for the removal of Zn, Cd and Pb from a water solution. The presented results do not confirm the effect of competing metal ions on the sorption efficiency of the selected metals by the investigated biochars. Based on that, the studied biochar sorbents can be used in environments contaminated with many metals.